The Girl Who Loved Coyotes - Nancy Wood (U.S.A Morrow Junior Books, 1995)
The American Southwest is a land of legend, the meeting place of Indian, Spanish, and Anglo cultures. Within these 12 tales coyotes turn into stars, rainbows carry dreams across vast canyons, and an eagle brings fire to the world. Full color.
Keywords: Read Aloud -- Read Aloud